An attempt to reduce the mental impacts of current COVID-19 pandemic across the globe - Momin, Aadil A. (International Journal Of Community Medicine And Public Health, 2022)
This article is nothing but a theoretical attempt to reduce the negative impacts which have been produced in the minds of the people across the globe due to coincident COVID-19 pandemic and sudden enormously elongated lockdowns. All these sudden lockdowns not only disturbed the routine lives but also weakened the financial statuses of the middle class families. The poverty ratio, hunger index and deaths caused by starvation have been greatly increased, especially in under-developed and developing countries. The personal views and comments are presented in this article which will help the readers scientifically as well as psychologically to improve their mental health.